Baroreflex Sensitivity after Adenotonsillectomy in Children with Obstructive Sleep Apnea during Wakefulness and Sleep - Crisalli, Joseph A. (Associated Professional Sleep Societies, LLC, 2012)
STUDY OBJECTIVES: Children with obstructive sleep apnea have blunted baroreflex sensitivity and increased blood pressure variability. The aim of the study was to test the hypothesis that treatment of sleep apnea by adenotonsillectomy results in significant improvement of baroreflex sensitivity, lowering of blood pressure and blood pressure variability and increase vagal heart rate modulation. STUDY DESIGN: One hundred ninety-four children aged 9.6 ± 2.3 years were enrolled; 133 had obstructive sleep apnea and 61 were healthy controls. For children with sleep apnea, polysomnography with 3-lead electrocardiography and continuous blood pressure was performed before adenotonsillectomy, then 6 weeks and 6 months postoperatively. Controls underwent the same assessment at study entry and 6 months later. Spontaneous baroreflex sensitivity was measured in the time and frequency domains. Data analyses were performed for available and complete cases. RESULTS: Children with sleep apnea experienced postoperatively an increase in baroreflex sensitivity and decrease in blood pressure variability during wakefulness and sleep. A decrease in blood pressure during sleep and in heart rate during wakefulness was also measured. The improvement in baroreflex sensitivity was predicted by the change in the apnea-hypopnea and arousal indices. A normal pattern of rising baroreflex sensitivity during the night was restored in children with severe apnea after surgery. However, baroreceptor sensitivity did not completely normalize after treatment. CONCLUSION: Treatment of obstructive sleep apnea in children by adenotonsillectomy is associated with gradual improvement in known risk factors for cardiovascular disease. Complete normalization of baroreceptor sensitivity was not achieved 6 months postoperatively. CITATION: Crisalli JA; McConnell K; VanDyke RD; Fenchel MC; Somers VK; Shamszumann A; Chini B; Daniels SR; Amin RS. Baroreflex sensitivity after adenotonsillectomy in children with obstructive sleep apnea during wakefulness and sleep. SLEEP 2012;35(10):1335-1343.